2022
DOI: 10.1021/acs.jpcc.2c05903
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Gold Stacked Layers as Substrates for SERS Detection in Liquids or Gases with Ultralow Detection Limits and Long-Term Stability

Abstract: Surface-enhanced Raman scattering (SERS) substrates consisting of stacked ultrathin nanoporous gold layers are used to detect very low concentrations of molecules in liquids or gases. The SERS substrates are obtained by copper chemical etching of alternative copper and gold stacked nanolayers. This process is a reliable method for fabricating uniform and reproducible SERS substrates, with a robust SERS response at extremely low detection limits. By optimizing fabrication conditions combined with a thorough ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…For the dealloyed films, the observed porosity is attributed to the removal of copper atoms from the alloy combined with the Au surface diffusion process during the dealloying, resulting in the formation of a planar gold skeleton consisting of nanopores and interconnected nanoligaments . For the transferred pure Au films, the formation of pores and ligaments for the 13 nm-Au transferred sample is attributed to the reorganization of the very thin Au layer during the etching of Cu sacrificial layer as it has already been observed in previous works. , Indeed, below a few tens of nm in thickness, the thermodynamic instability leads to a reorganization of their nanostructure . On the other hand, thicker films are thermodynamically more stable.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…For the dealloyed films, the observed porosity is attributed to the removal of copper atoms from the alloy combined with the Au surface diffusion process during the dealloying, resulting in the formation of a planar gold skeleton consisting of nanopores and interconnected nanoligaments . For the transferred pure Au films, the formation of pores and ligaments for the 13 nm-Au transferred sample is attributed to the reorganization of the very thin Au layer during the etching of Cu sacrificial layer as it has already been observed in previous works. , Indeed, below a few tens of nm in thickness, the thermodynamic instability leads to a reorganization of their nanostructure . On the other hand, thicker films are thermodynamically more stable.…”
Section: Resultssupporting
confidence: 66%
“…30 For the transferred pure Au films, the formation of pores and ligaments for the 13 nm-Au transferred sample is attributed to the reorganization of the very thin Au layer during the etching of Cu sacrificial layer as it has already been observed in previous works. 37,38 Indeed, below a few tens of nm in thickness, the thermodynamic instability leads to a reorganization of their nanostructure. 39 On the other hand, thicker films are thermodynamically more stable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The behavior of the SERS response is comparable to that reported in the literature and can be related to the adsorption isotherm curve of RhB [ 49 50 ]. The plateau in the SERS response observed between 10 −8 and 10 −10 mol·L −1 can be assigned to either the saturation of the chemical sites (i.e., no supplementary absorption is made) or to the fact that RhB continued to be absorbed outside of the hot spot [ 6 , 51 ]. Comparing the integrated intensity of the RhB peak, it can be observed that the intensity of the signal is lower for the sample dealloyed in H 3 PO 4 than that for the sample dealloyed in HCl.…”
Section: Resultsmentioning
confidence: 99%